Defamation on Social Media: A Review of Article 1365 of the Indonesian Civil Code - Atika Sunarto; Ahmad Taris Arrofi; Muhammad Ali Adnan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
The development of social media as a digital public space brings both benefits and legal risks, particularly concerning defamation. Under Indonesian civil law, such acts can be classified as unlawful acts based on Article 1365 of the Indonesian Civil Code, which obliges the perpetrator to compensate for damages. This study aims to analyze legal policies regarding defamation on social media and the implementation of Article 1365 of the Civil Code in practice. The method used is normative juridical, examining legislation, legal doctrines, and judicial practice. The results indicate that Article 1365 plays a crucial role in providing legal protection, both for material and immaterial losses. However, its application faces challenges, including evidence collection, identification of anonymous perpetrators, and the limited capacity of law enforcement authorities. Strengthening digital literacy and supporting cyber-legal infrastructure are necessary to ensure the effectiveness of legal protection for victims.